2020
DOI: 10.1111/bph.14997
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the anti‐hyperalgesic effects of cannabidiolic acid‐methyl ester in a preclinical model of peripheral neuropathic pain

Abstract: Background and Purpose: Chronic neuropathic pain (NEP) is associated with growing therapeutic cannabis use. To promote quality of life without psychotropic effects, cannabinoids other than Δ9-tetrahydrocannabidiol, including cannabidiol and its precursor cannabidiolic acid (CBDA), are being evaluated. Due to its instability, CBDA has been understudied, particularly as an anti-nociceptive agent. Adding a methyl ester group (CBDA-ME) significantly enhances its stability, facilitating analyses of its analgesic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…This finding was in line to the synthesis of cannabidiolic acid methyl ester (HU-580), whose chemical features, slightly different from its natural precursor, seem to encompass CBDA chemical instability, and its susceptibility to decarboxylation [37]. Recent findings state that HU-580 also positively affects the sleep-wake cycle in male Wistar rats [38], and still CBDA anti-nociceptive activity was enhanced following methyl ester group addition [39]. The potential CBDA anti-inflammatory activity continues to be the main focus for deepened investigations.…”
Section: Cbda As Bioactive Compoundsupporting
confidence: 65%
“…This finding was in line to the synthesis of cannabidiolic acid methyl ester (HU-580), whose chemical features, slightly different from its natural precursor, seem to encompass CBDA chemical instability, and its susceptibility to decarboxylation [37]. Recent findings state that HU-580 also positively affects the sleep-wake cycle in male Wistar rats [38], and still CBDA anti-nociceptive activity was enhanced following methyl ester group addition [39]. The potential CBDA anti-inflammatory activity continues to be the main focus for deepened investigations.…”
Section: Cbda As Bioactive Compoundsupporting
confidence: 65%
“…In females, none of the cannabis-derived oil formulations tested in the current investigation prevented the onset or further progression of mechanical hypersensitivity in response to sustained peripheral nerve constriction. Using the nerve cuff model, our group has observed a similar sexual dimorphism in behavioural treatment responsiveness to intraperitoneally injected cannabidiolic acid (CBDA)-methyl ester, a stabilized form of naturally derived CBDA that is a precursor of CBD [46].…”
Section: Plos Onementioning
confidence: 96%
“…The acute intracellular electrophysiological recording techniques have been reported previously in animal models of NP [40,41,43,46] and cancer pain [47,48]. After the last behavioural test was performed during week 9 (day 63 post-nerve cuff surgery), each rat was initially anesthetised with an intraperitoneally delivered mixture of acepromazine, ketamine, and xylazine.…”
Section: In Vivo Intracellular Drg Recordingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies based on sciatic nerve injury in rodents are frequently used to cost-effectively provide a model of neuropathic pain [37] and are therefore being used to examine sexually dimorphic outcomes. Indeed, behavioral and electrophysiological research by our group has shown that this type of pain persists in female rodents, while males respond well to various agents that have been tested to date [38][39][40].…”
Section: Persistent Sciatic Nerve Painmentioning
confidence: 99%